뇌졸중 후 경련성 편마비의 침치료에 대한 최신 임상 연구 동향 - CAJ 검색을 중심으로 - 조명재(Myeong Jae Jo); 김다혜(Da Hye Kim); 김선우(Seon U Kim); 박철우(Cheol U Park); 김영광(Young Kwang Kim); 장혜연(Hye Yeon Jang); 김민욱(Min Uk Kim) (동의생리병리학회지, 2021)
To analyze the clinical efficacy of acupuncture for spastic hemiplegia after stroke, this study was accomplished by considering Randomized Controlled Trials. We searched for papers that performed acupuncture for spastic hemiplegia after stroke in the China Academic Journal of the China National Knowledge Infrastructure, from January 1, 2017 to June 30, 2020. In total, 23 reports were included in this review. There are 18 studies conducted with more than 50 subjects and less than 100 subjects. The largest number of treatment was 20 times. 28days(4weeks) was the largest number of treatment period, which accounted 10 studies. The most frequently used evaluation index was The Fugl-Meyer Assessment(FMA) and Clinical Efficacy, each used 21 times and 17 times. The most frequently used acupuncture point was LI3, which was used 13 times. The retention time was 30 minutes and 11 studies were conducted. Western medicine treatment was the most common control group in 15 studies. Most of studies showed result of the intervention group was statistically significant, compared with the control group. These results suggest that acupuncture for spastic hemiplegia after stroke was effective and it was statistically more significant than the control group. However, it is difficult to confirm a conclusion, because the quality of most of studies was low.